(untitled) (Fiep Bulletin - online, 2013)
This is a literature, historical and conceptual feminist movements in the XX and XXI centuries, based on the work referenced. We tried to extract important considerations in the study of the evolution of civil rights and women’s claims, particularly in Brazil. The opinions issued by the aforementioned authors, mostly women, have an epistemological language, besides being precise sources of data and broad thematic spectrum.